Structural insights into opposing actions of neurosteroids on GABAA receptors - Dagimhiwat H. Legesse; Chen Fan; Jinfeng Teng; Yuxuan Zhuang; Rebecca J. Howard; Colleen M. Noviello; Erik Lindahl; Ryan E. Hibbs (Nature Communications, 2023)
Abstract γ-Aminobutyric acid type A (GABAA) receptors mediate fast inhibitory signaling in the brain and are targets of numerous drugs and endogenous neurosteroids. A subset of neurosteroids are GABAA receptor positive allosteric modulators; one of these, allopregnanolone, is the only drug approved specifically for treating postpartum depression. There is a consensus emerging from structural, physiological and photolabeling studies as to where positive modulators bind, but how they potentiate GABA activation remains unclear. Other neurosteroids are negative modulators of GABAA receptors, but their binding sites remain debated. Here we present structures of a synaptic GABAA receptor bound to allopregnanolone and two inhibitory sulfated neurosteroids. Allopregnanolone binds at the receptor-bilayer interface, in the consensus potentiator site. In contrast, inhibitory neurosteroids bind in the pore. MD simulations and electrophysiology support a mechanism by which allopregnanolone potentiates channel activity and suggest the dominant mechanism for sulfated neurosteroid inhibition is through pore block.